PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI GAMIFIKASI DALAM PEMBELAJARAN KELAS V SEKOLAH DASAR - Desta Widyawati, Arum; Merlin Claudia, Deva; Qotimah, Khusnul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve the learning motivation of fifth-grade students at SDN 182/I Hutan Lindung through the implementation of gamification using Canva-based leveled game media. The research design used was Classroom Action Research (CAR) conducted in one cycle with two meetings. Research subjects were 16 fifth-grade students. Data were collected through observation sheets and learning motivation questionnaires. The results showed an increase in average student learning motivation from 41.9% in the pre-cycle to 75.5% in the post-action of cycle I, with all success indicators achieved. The application of gamification elements such as points, badges, leaderboards, and level-based challenges proved effective in creating an enjoyable learning atmosphere, increasing active participation, satisfaction, and student confidence. These findings prove that gamification is an innovative and relevant approach to be applied in elementary school learning in accordance with the principles of the Independent Curriculum.